EFFECT OF DIE GEOMETRY ON THE STRUCTURAL DEVELOPMENT OF A THERMOTROPIC LIQUID-CRYSTALLINE POLYMER IN A THERMOPLASTIC ELASTOMER MATRIX - SEO, Y; HWANG, SS; HONG, SM; PARK, TS; KIM, KU (SOC PLASTICS ENG INC, 1995)
This study investigates deformation of a thermotropic liquid crystalline polymer (TLCP) in different die geometries. Blends of a TLCP with a thermoplastic elastomer of EPDM were made in a twin-screw extruder. Morphological observation of the extruded blends demonstrates the complimentary effect of shear in the die exit on dispersed phase deformation and fibril formation. Shea. strain can affect fibril formation for a relatively large dispersed phase in the region close to the die wall. However, the main role of shearing is in breaking up the larger particles and initial polydomain structure. A strong elongational deformation on the blended melt after the die exist is required, and fine microfibrils normally observed in in situ composites were not easily formed by shear deformation only in the die.
Keywords: INSITU COMPOSITES; ASPECT RATIO; BLENDS; MORPHOLOGY; FLOW; COPOLYESTER; SHEAR